Identification of GOLDEN2-like transcription factor genes in soybeans and their role in regulating plant development and metal ion stresses - Alam, Intikhab; Manghwar, Hakim; Zhang, Hanyin; Yu, Qianxia; Ge, Liangfa (Frontiers in Plant Science, 2022)
The Golden 2-Like (G2-like or GLK) transcription factors are essential for plant growth, development, and many stress responses as well as heavy metal stress. However, G2-like regulatory genes have not been studied in soybean. This study identified the genes for 130 G2-Like candidates’ in the genome of Glycine max (soybean). These GLK genes were located on all 20 chromosomes, and several of them were segmentally duplicated. Most GLK family proteins are highly conserved in Arabidopsis and soybean and were classified into five major groups based on phylogenetic analysis. These GmGLK gene promoters share cis-acting elements involved in plant responses to abscisic acid, methyl jasmonate, auxin signaling, low temperature, and biotic and abiotic stresses. RNA-seq expression data revealed that the GLK genes were classified into 12 major groups and differentially expressed in different tissues or organs. The co-expression network complex revealed that the GmGLK genes encode proteins involved in the interaction of genes related to chlorophyll biosynthesis, circadian rhythms, and flowering regulation. Real-time quantitative PCR analysis confirmed the expression profiles of eight GLK genes in response to cadmium (Cd) and copper (Cu) stress, with some GLK genes significantly induced by both Cd and Cu stress treatments, implying a functional role in defense responsiveness. Thus, we present a comprehensive perspective of the GLK genes in soybean and emphasize their important role in crop development and metal ion stresses.